2018
DOI: 10.1017/s1472669618000063
|View full text |Cite
|
Sign up to set email alerts
|

Data Protection in UK Library and Information Services: Are We Ready for GDPR?

Abstract: Against a backdrop of increasing data security and privacy concerns, current data protection law will soon be overhauled by the General Data Protection Regulation (GDPR). Previous research has indicated a lack of data protection management in libraries, however, it has been nine years since the latest study. This article by Josephine Bailey aims to provide an updated review of the extent of data protection management in UK library and information services and gauge preparation for the incoming GDPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Influences on the writings of other Victorian figures may be successfully analysed using our method, but this is not the case for more recent authors, due to the '20th century black hole' in our digitized cultural heritage (Fallon and Uceda Gomez, 2015). It is also unlikely that researchers will be able to access the borrowing records of modern writers without explicit consent, due to changes in privacy legislation and the resulting appropriate responses from the library sector (Bowers, 2006;Dowling, 2017;Bailey, 2018): it is unlikely that modern reading records will survive to enable this type of research. We therefore suggest that this method is applicable to the reading and writing of authors beyond Mill, but is most likely to succeed, or even only be possible, for other leading figures professionally active from the mid-eighteenth to early-twentieth centuries.…”
Section: Discussionmentioning
confidence: 99%
“…Influences on the writings of other Victorian figures may be successfully analysed using our method, but this is not the case for more recent authors, due to the '20th century black hole' in our digitized cultural heritage (Fallon and Uceda Gomez, 2015). It is also unlikely that researchers will be able to access the borrowing records of modern writers without explicit consent, due to changes in privacy legislation and the resulting appropriate responses from the library sector (Bowers, 2006;Dowling, 2017;Bailey, 2018): it is unlikely that modern reading records will survive to enable this type of research. We therefore suggest that this method is applicable to the reading and writing of authors beyond Mill, but is most likely to succeed, or even only be possible, for other leading figures professionally active from the mid-eighteenth to early-twentieth centuries.…”
Section: Discussionmentioning
confidence: 99%
“…From previous empirical research in libraries, it can be concluded that ethical codes of libraries do not provide adequate answers or tools for the modern use of information and communication technologies in libraries (Ferguson et al, 2016), that privacy is a frequent source of ethical dilemmas and concerns in libraries (Sturges et al, 2003;Corrado, 2020), and libraries are not fully prepared for the challenges related to privacy and personal data protection (Bailey, 2018;Corrado, 2020).…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…In this paper, the APCO Macro Model is used to explore the factors of information privacy culture in libraries. This examination is done from the perspective of librarians, for the reason that certain factors of the model (awareness of privacy, librarians' attitudes, experiences, handling of personal data, knowledge of regulations) are in the context of libraries previously researched separately (Magi, 2007;Schepmann et al, 2008;Sturges et al, 2003;Zimmer, 2014;Tummon and McKinnon, 2018;Bailey, 2018), as well as a construct that was considered in the broader domain of privacy (confidence towards the data protection authority). In addition, to test the hypothesis, the construct "library size" is examined, whereby the size is determined by the number of librarians in the library and the number of active users.…”
Section: Conceptual Model Used In Researchmentioning
confidence: 99%
“…Ahead of the entry into force of the GDPR, a UK survey on the level of library readiness for GDPR implementation showed an improvement over the survey conducted nine years earlier, librarians' awareness of the new legal framework and several key aspects. However, librarians still participate very little in the organization of personal data protection management, and 48% do not know if they have a privacy policy in the library although 85% of them consider this topic to be extremely important (Bailey, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%